KEWENANGAN PENYELESAIAN SENGKETA TATA USAHA NEGARA TERHADAP PUTUSAN PEMBERHENTIAN TIDAK DENGAN HORMAT - Muten Nuna; Roy Marthen Moonti; Arifin Tumuhulawa; Dince Aisa Kodai (Universitas Bengkulu, 2020)
Nowadays, Indonesia as a developing country has been developed in various sectors. Globalization is a process of organizational change from the function of capitalism which is marked by the emergence of the integration of markets and transnational companies and the lagging of supranational institutions. With this, it is possible for it to affect the work patterns of Indonesian society. For this reason, a further legal remedy will be needed if the party that feels disadvantage is not satisfied with the outcome of the dispute resolution that arises due to the development of globalization. The intended legal remedies are administrative efforts as referred to in Article 48 of Law Number 51 of 2009 concerning Amendments to Law Number 9 of 2004 concerning Amendments to Law Number 5 of 1986 concerning State Administrative Court (PTUN). The aim of this article is to find out the authority for dispute resolution of State Administrative Court (PTUN) toward dismissal with no reverence verdict and dispute resolution efforts for State Administrative Court (PTUN) toward dismissal with no reverence verdict. Juridical normative is applied as research method. This research concludes that dispute resolution on personnel is done through the State Administrative Court except it is caused by violations of the disciplinary rules of the State Civil Apparatus which will be resolved through administrative appeals to the Court of Civil Service.